2005
DOI: 10.1112/s0024610705006769
|View full text |Cite
|
Sign up to set email alerts
|

The Sum-of-Digits Function of Squares

Abstract: Abstract. We consider the set of squares n 2 , n < 2 k , and split up the sum of binary digits s(n 2 ) into two parts s [ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
23
0
2
Order By: Relevance
“…By Lemma 3.1, we thus have (q − 1)|u and so (q − 1)|u 2 . By Lemma 3.1 again, we have (q − 1)|s q (u 2 ) and so (q − 1)|e 1 . Let e 3 = e 2 /(q − 1) and e 4 = e 1 /(q − 1) so that s q (u) = (q − 1)(k(m + 1) + n + e 3 ) and s q (u 2 ) = (q − 1)(n − mk + e 4 ).…”
Section: General Basementioning
confidence: 99%
See 1 more Smart Citation
“…By Lemma 3.1, we thus have (q − 1)|u and so (q − 1)|u 2 . By Lemma 3.1 again, we have (q − 1)|s q (u 2 ) and so (q − 1)|e 1 . Let e 3 = e 2 /(q − 1) and e 4 = e 1 /(q − 1) so that s q (u) = (q − 1)(k(m + 1) + n + e 3 ) and s q (u 2 ) = (q − 1)(n − mk + e 4 ).…”
Section: General Basementioning
confidence: 99%
“…Other work was done by Drmota and Rivat [1] in studying the binary digits of squares. They showed that for any k if one takes the set of squares n 2 such that n < 2 k , we have that the two sets of numbers #{n < 2 k : s ≥k (n 2 ) = m} and #{n < 2 k : s <k (n 2 ) = m} are asymptotically equidistributed in residue classes where s |<k| (n 2 ) = s 2 (n 2 mod 2 k ) represents the sum of the rightmost k digits in n 2 and s |≥k| (n 2 ) = s 2 (⌊n 2 /2 k ⌋) represents the sum of the remaining digits.…”
Section: Introductionmentioning
confidence: 99%
“…La fonction f ainsi définie est clairement périodique de période q . Cette fonction tronquée apparaît dans un contexte différent dans [12] où Drmota et Rivat etudient certaines propriétés de f .n 2 / lorsque est de l'ordre de log n. LEMME 5. Pour tout " > 0, il existe une constante c."/ telle que pour tous , , entiers avec > 0, > 0 et 0 6 6 =2, pour tout r 2 ‫ޚ‬ avec jrj < q , le nombre E.r; ; ; / de couples d'entiers .m; n/ tels que q 1 < m 6 q , q 1 < n 6 q et…”
Section: Sommes De Type IIunclassified
“…also [5] and [6]). We directly derive asymptotic expansions for moments (Corollary 2) and a refinement of the central limit theorem stated in Corollary 1, further a local limit theorem (Corollary 3), uniform distribution in residue classes (Corollary 4) and uniform distribution modulo 1 (Corollary 5).…”
Section: A Dirichlet Series Methodmentioning
confidence: 99%